Response to pioglitazone in non-alcoholic fatty liver disease patients with vs. without type 2 diabetes: A meta-analysis of randomized controlled trials - Wang, Zeyu; Du, Huiqing; Zhao, Ying; Ren, Yadi; Ma, Cuihua; Chen, Hongyu; Li, Man; Tian, Jiageng; Xue, Caihong; Long, Guangfeng; Xu, Meidong; Jiang, Yong (Frontiers in Endocrinology, 2023)
Background: Pioglitazone is considered the potential therapy for NAFLD. However, different effects of pioglitazone on NAFLD have been demonstrated in diabetic and non-diabetic patients. Herein, a meta-analysis of randomized, placebo-controlled trials was carried out to indirectly compare the pioglitazone in NAFLD patients with vs. without type 2 diabetes. Methods: The randomized controlled trials (RCTs) of pioglitazone vs. placebo involving NAFLD patients with or without type 2 diabetes/prediabetes collected from the databases were enrolled into this analysis. Methodological quality was employed to evaluate the domains recommended by the Cochrane Collaboration. The analysis covered the changes in histology (fibrosis, hepatocellular ballooning, inflammation, steatosis), liver enzymes, blood lipids, fasting blood glucose (FBS), Homeostasis model assessment-IR (HOMA-IR), weight and body mass index (BMI) before and after treatment, and adverse events. Results: The review covered 7 articles, 614 patients in total, of which 3 were non diabetic RCTs. No difference was found in patients with vs. without type 2 diabetes in histology, liver enzymes, blood lipids, HOMA-IR, weight, BMI and FBS. And no significant difference was revealed in adverse effects between NAFLD patients with diabetes and without DM, except the incidence of edema was found to be higher in the pioglitazone group than in the placebo group in NAFLD patients with diabetes. Conclusions: Pioglitazone could exert a certain effect on alleviating NAFLD, which was consistent between non-diabetic NAFLD patients and diabetic NAFLD patients in improving histopathology, liver enzymes and HOMA-IR, reducing blood lipids. What's more, no adverse effects will be raised, except the incidence of edema is higher in the pioglitazone group in NAFLD patients with diabetes. However, Large sample sizes and well-designed RCT studies are required to further confirm these conclusions.